Factors Related to Quality of Life in Hemodialysis Patients - Adhin Al Kasanah; Faqih Nafiul Umam; Mega Arianti Putri (Jurnal Ilmu Keperawatan Jiwa, 2021)
Hemodialysis therapy is a long-term therapy in patients with chronic kidney disease that can affect the patient's quality of life. Quality of life is an important indicator that shows the well-being of hemodialysis patients. Identification of factors related to quality of life can help patients and health workers in making decisions regarding health problems. The purpose of this study was to determine the factors associated with the quality of life of hemodialysis patients. This study is a cross-sectional study involving 77 hemodialysis patients at RSUD Madiun. The sampling technique used is purposive sampling technique. Quality of life was assessed by the WHOQOL-Bref which consists of four domains containing 26 statement items. Statistical analysis used linear regression. The average value of quality of life in this study was 58.58 ± 14.27, which means that it is in the category of moderate quality of life. Factors related to the quality of hemodialysis patients were duration of hemodialysis (p=0.00) and living status (p=0.00). The value of R square was 58.7, which means that the variable duration of hemodialysis and living status affected the quality of life of HD patients by 58.7%.. Duration of hemodialysis and living status are factors related to the quality of life of hemodialysis patients.